Miticidal Evaluation of Different Non-Volatile Bioactive Compounds Extracted from Ferula Oopoda Against Apple Mites - Saeed, Ahmed; Baloch, Nizam; Qambrani, Taimur; Khan, Sheraz; Khan, Shahbaz; Asif, Muhammad (Al-Nahrain Journal of Science, 2021)
The research was administered in order to spot the miticidal effect of wild grown plant namely Ferula oopoda against the mites that destroy the leaf tissue and also the colour of the fruit in trees. The theme was to get the herb’s (1) aerial, stem and root part about 1 kg and was soaked for about 7 days and then extract the oil by the help of vaccum rotary evaporator, the extracted oil is then allowed to stay for a day in HCl (0.2M), then the solution is filtered and then some charcoal is added to the filtrate and now, it is put on the Bunsen burner for a while, now the HCl extract is again filtered and basified by the addition of Sodium hydroxide (5M), the yellow colour is the indication of basification and now the ppts are collected that are formed over the filter paper, the ppts are dried and later on sprayed on the apple mites and their mortality rates are noted at exposure time of 6, 12, 24, 36 and 48h. It may be a new revolutionary technique that can be economical as well as environment friendly as the oil is only lethal for the target apple mites and doesn’t not harm human health.